Nine new species of the "aeruginosus"-group in Amynthas (Clitellata: Megascolecidae) from Nam Et-Phouley National protected Area, Laos - Hong, Yong; Inkhavilay, Khamla; James, Samuel W. (Zootaxa, 2018)
Nine new species of Amynthas (Clitellata: Megascolecidae) from Mt. Phouleoi, Lao PDR: Earthworm specimens were collected on the top of Mt. Phouleoi, Viengthong District, Houaphanh province, Lao PDR. The new species belonged to pheretimoid earthworms. They have spermathecal pores in 7/8 and 8/9, corresponding to the aeruginosus-group as characterized by Sims and Easton (1972). Their names are: Amynthas bouatongi sp. nov., Amynthas hoauykanangensis sp. nov., Amynthas phimpheti sp. nov., Amynthas nametensis sp. nov., Amynthas somechanae sp. nov., Amynthas wiggeri sp. nov., Amynthas fleischmani sp. nov., Amynthas antethecus sp. nov., and Amynthas elenabondae sp. nov. With the exception of A. nametensis sp. nov., all have the first dorsal pore in an unusually anterior location close to 5/6 and very large, often coiled, prostatic ducts. Several species have slight intraparietal invaginations of the primary male pores, but the similarity of other characters leads us to include them in Amynthas rather than in a polyphyletic Metaphire. Amynthas bouatongi sp. nov. has male pores 0.20–0.24 circumference apart on reniform male pads, pair genital papillae medial and lateral to male pores in XVIII. Amynthas hoauykanangensis sp. nov. has openings of copulatory pouches 0.19–0.25 circumference apart, and paired round genital papillae on postsetal XVII and presetal XIX in line with the male pores. Amynthas phimpheti sp. nov. has male pores 0.21–0.24 circumference apart, round thickened genital papillae paired on 17/18 and 18/19 in line with male pores. Amynthas nametensis sp. nov. has male pores superficial on thickened circular pads, 0.24–0.27 circumference apart. Amynthas somechanae sp. nov. has male pores 0.20–0.33 circumference apart, and paired equatorial papillae in XVIII. Amynthas wiggeri sp. nov. has male pores 0.22–0.30 circumference apart, paired genital papillae equatorial on XVIII medial to male pores and paired papillae equatorial in XVII and XIX. Amynthas fleischmani sp. nov. has openings of copulatory pouches 0.24 circumference apart, paired conical genital papillae equatorial on XVII and XIX; paired circular papillae in intersegmental furrows of 17/18 and 18/19. Amynthas antethecus sp. nov. has openings of copulatory pouches 0.31 circumference apart, paired circular papillae in intersegmental furrow of 17/18 and equatorial on XIX, slightly medial to secondary male pores. Amynthas elenabondae sp. nov. has openings of copulatory pouches 0.19 circumference apart, crescent, convex medially; primary male pore on tubercle on lateral wall of shallow parietal invagination.